Exploring Core Addiction Themes and Their Resolution in Recovery Narratives Using the "Life as a Film" (LAAF) Procedure. Issue 4 (2nd October 2022) - Rowlands, David; Youngs, Donna; Canter, David
Abstract: Though narrative studies have provided important insights on addiction and recovery, social desirability and self-protective factors may limit the richness and relevance of standard "life story" accounts. In marginalized populations, the "Life as Film" (LAAF) procedure has proved useful for addressing these concerns. Building on this literature, the present study adopted the LAAF approach with an objective to undercover features distinguishing addiction and recovery narratives. Achieving this objective serves to model addiction and recovery in terms of narrative constructions and reconstructions. Thirty-two participants, active or in recovery from addiction, were recruited, producing LAAF narratives of their lives. Interviewees completed a Recovery Inventory (RI), to compare narrative material with recovery outcomes. Content analysis revealed three structures: (1) a high prevalence Core Plot, featuring interpersonal conflict, negative arousal and self-management via substance use; (2) an Addiction Narrative, with themes of victimization, betrayal, compulsion, and escapist protagonists; and (3) a Recovery Narrative, with themes of redemption, self-mastery, caring, unity, and healer protagonists. Findings build on existing literature, suggesting narrative processes through which core conflicts become embedded in addiction stories and resolved in recovery stories. These processes indicate psychological pathways to positive change, carrying implications for interventions.